1996
DOI: 10.1029/96gb02692
|View full text |Cite
|
Sign up to set email alerts
|

An integrated biosphere model of land surface processes, terrestrial carbon balance, and vegetation dynamics

Abstract: Here we present a new terrestrial biosphere model (the Integrated Biosphere Simulator ‐ IBIS) which demonstrates how land surface biophysics, terrestrial carbon fluxes, and global vegetation dynamics can be represented in a single, physically consistent modeling framework. In order to integrate a wide range of biophysical, physiological, and ecological processes, the model is designed around a hierarchical, modular structure and uses a common state description throughout. First, a coupled simulation of the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
949
0
25

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,206 publications
(985 citation statements)
references
References 98 publications
11
949
0
25
Order By: Relevance
“…We analyzed the relationship of LAI and ET/ET 0 in GLE and LSP for both Tamarix stand and Populus stand. According to the approximate method commonly used, the daily LAI values were set to be linearly increased with time in GLE, and linearly declined with time in LSP (Foley et al, 1996). The results showed that ET/ET 0 was significantly linearly correlated with LAI ( Figure 6).…”
Section: Key Control Factors On the Spatial Variations Of Etmentioning
confidence: 93%
“…We analyzed the relationship of LAI and ET/ET 0 in GLE and LSP for both Tamarix stand and Populus stand. According to the approximate method commonly used, the daily LAI values were set to be linearly increased with time in GLE, and linearly declined with time in LSP (Foley et al, 1996). The results showed that ET/ET 0 was significantly linearly correlated with LAI ( Figure 6).…”
Section: Key Control Factors On the Spatial Variations Of Etmentioning
confidence: 93%
“…To our knowledge, interactions in which land use affects forest ecosystems on this scale have been considered only implicitly through the use of historical land-use and land-cover databases in ecological simulations (Reiners et al, 2002;VEMAP, 1995;Foley et al, 1996;and Houghton et al, 1999). Antle et al, (2001) have created a similar coupled model that focuses on C-sequestration in agricultural soil.…”
Section: Conceptsmentioning
confidence: 99%
“…West Africa is defined here as the region between the Sahara desert to the north and the Atlantic coast to the south, between 15°W and 15°E. Savannas occupy wide areas of West Africa, as seen in Figure 3, roughly located between 7°a nd 12.5°N [Anderson et al, 1976;Foley et al, 1996].…”
Section: Study Areamentioning
confidence: 99%
“…One experiment is performed only using the biospheric model, and the other is carried out by asynchronous coupling of the biospheric model and distributed hydrologic model. The biospheric model is the Integrated Biosphere Simulator (IBIS) [Foley et al, 1996] which describes biophysical, physiological, and ecological processes. The distributed hydrologic modeling is performed using Systeme Hydrologique Europeen (SHE) [Abbott et al, 1986a[Abbott et al, , 1988b.…”
Section: Modelsmentioning
confidence: 99%